2016
DOI: 10.1007/s11999-015-4563-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Pars Defects at the L4 Vertebra Result in Increased Degeneration When Compared With Those at L5: An Anatomic Study

Abstract: Background Cadaveric studies have examined disc degeneration at the L4-L5 and L5-S1 motion segments; however, we are not aware of another study that has examined the relationship between bilateral spondylolysis and its effect on degenerative disc disease at those levels. This may have been overlooked by researchers owing to the majority of spondylolysis occurring at the L5 vertebra. Questions/purposes Using osteologic specimens from a collection that included individuals who died in one city in the USA between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
2
4
0
1
Order By: Relevance
“…However, DDG, SR, and ODI showed no significant differences in our study, even when accounting for age. This result was discordant with the conclusions and speculations of previous anatomical studies [6]. The disagreement was caused mainly by difference in study subjects; the subjects in our study were in urgent need of interventions while those in previous anatomical studies had no clinical symptoms or only mild symptoms.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, DDG, SR, and ODI showed no significant differences in our study, even when accounting for age. This result was discordant with the conclusions and speculations of previous anatomical studies [6]. The disagreement was caused mainly by difference in study subjects; the subjects in our study were in urgent need of interventions while those in previous anatomical studies had no clinical symptoms or only mild symptoms.…”
Section: Discussionsupporting
confidence: 53%
“…Grobler et al [5] performed biomechanical experiments on six specimens to confirm that the lesion segment was more unstable when spondylolytic lesions occurred at L4 than at L5. Through an observational study on 665 skeletal lumbar spines, McCunniff et al [6] found that patients with spondylolysis at L4 also displayed a greater degree of degeneration of the disc below the level of the associated isthmic defect than those with spondylolysis at L5, suggesting that there was a greater degree of degenerative disc disease and clinical symptoms among people with spondylolysis at L4. Most patients with spondylolysis progressed to IS when they had obvious clinical symptoms [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, DDG, SR, and ODI showed no signi cant differences in our study, even when accounting for age. This result was discordant with the conclusions and speculations of previous anatomical studies [6]. The disagreement was caused mainly by difference in study subjects; the subjects in our study were in urgent need of interventions while those in previous anatomical studies had no clinical symptoms or only mild symptoms.…”
Section: Disscussionsupporting
confidence: 53%
“…Grobler et al [5] performed biomechanical experiments on six specimens to con rm that the lesion segment was more unstable when spondylolytic lesions occurred at L4 than at L5. Through an observational study on 665 skeletal lumbar spines, McCunniff et al [6] found that patients with spondylolysis at L4 also displayed a greater degree of degeneration of the disc below the level of the associated isthmic defect than those with spondylolysis at L5, suggesting that there was a greater degree of degenerative disc disease and clinical symptoms among people with spondylolysis at L4. Most patients with spondylolysis progressed to IS when they had obvious clinical symptoms [7].…”
Section: Introductionmentioning
confidence: 99%
“…Grobler et al [5] performed biomechanical experiments on six specimens to confirm that the lesion segment was more unstable when spondylolytic lesions occurred at L4 than at L5. Through an observational study on 665 skeletal lumbar spines, McCunniff et al [6] found that patients with spondylolysis at L4 also displayed a greater degree of degeneration of the disc below the level of the associated isthmic defect than those with spondylolysis at L5, suggesting that there was a greater degree of degenerative disc disease and clinical symptoms among people with spondylolysis at L4.…”
Section: Introductionmentioning
confidence: 99%